Arctic Ark. Human-animal adaptations to the arctic environment: natural and folk selection practices (Arc-Ark) - Kantanen, Juha; Stammler, Florian; Ghanem, Nasser; Gossman-Stammler, Anna; Mazzullo, Nuccio; Peippo, Jaana; Reilas, Tiina; Soppela, Päivi; Tapio, Ilma; Honkatukia, Mervi
2015